2016
DOI: 10.1021/acs.molpharmaceut.6b00352
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Sensitivity of Cancer Stem Cells to Chemotherapy Using Functionalized Mesoporous Silica Nanoparticles

Abstract: Cancer stem cells (CSCs) are responsible for cancer drug resistance with high expression of ABCG2, which pumps the internalized chemotherapeutic out to escape drug-induced cytotoxicity. Here, we established a functionalized mesoporous silica nanoparticle (MSN) system to deliver shABCG2 and doxorubicin (Dox) synergistically. With excellent cell uptake and endosomal escape capacities, the dual-delivery carriers internalized shABCG2 and Dox into CSCs efficiently. ABCG2 depletion increased intracellular and intran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 33 publications
(73 reference statements)
1
18
0
Order By: Relevance
“…Cancer stem cells (CSCs) have been defined to be a small subset of cancer cells within the tumour bulk, exhibiting self-renewal and differentiation capacities3. CSCs may well contribute to tumour initiation, metastasis, recurrence, as well as drug resistance345. Liver CSCs can be enriched by some defined surface markers678.…”
mentioning
confidence: 99%
“…Cancer stem cells (CSCs) have been defined to be a small subset of cancer cells within the tumour bulk, exhibiting self-renewal and differentiation capacities3. CSCs may well contribute to tumour initiation, metastasis, recurrence, as well as drug resistance345. Liver CSCs can be enriched by some defined surface markers678.…”
mentioning
confidence: 99%
“…Gastric TICs are also optimal targets for gastric tumor targeting(SR Singh 2013). However, TICs are resistant to traditional drugs, with high expression of pump molecules like ABCG2(ZZ Chen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Durfee et al showed that MSNs-supported lipid bilayers (protocells) were capable of active targeting and delivery to individual leukemia cells (Durfee et al, 2016). Chen et al employed functionalized MSNs to enhance sensitivity of cancer stem cells to chemotherapy (Chen et al, 2016). Datz et al demonstrated that genetically designed biomolecular capping system for MSNs enabled receptor-mediated cell uptake and controlled drug release (Datz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%